The effect of distraction on pain perception during an endovenous thermal ablation procedure. (August 2016) - van Zandvoort, Carina EG; Toonder, Irwin M; Stoopendaal, Irma AJ; Wittens, Cees HA
Objectives: To determine whether audio and visual distraction can affect the pain perception of a patient undergoing endovenous thermal ablation under tumescent anesthesia. Methods: Patients underwent an endovenous thermal ablation procedure and were randomized into two groups: non-distraction (AVD−) and with distraction (AVD+). Visual analogue scale pain score and hospital anxiety depression scale scores were used to measure outcome. The recruited patients were asked to submit an anticipated visual analogue scale pain score prior to treatment as well as the actual experienced post-operative visual analogue scale pain score. Results: There was no significant difference between the AVD− and AVD+ groups post-operative pain score 2.85 (SD 1.7) versus 2.60 (SD 2.3), p  = 0.68. Pain score in women with distraction (AVD+) decreased from 3.81 to 2.42. The pain score in men with distraction (AVD+) increases from 1.88 to 2.82. In the AVD− group, a significant difference was found between men and women ( p  = 0.014). Disregarding gender, a significant difference was found between the anticipated pain score and the actual pain score in both the AVD− group ( p  = 0.009) and AVD+ group ( p  = 0.021). There was a correlation between depression and the pain score, which was not seen between pain and anxiety score. Conclusion: The results suggested that audiovisual distraction has no influence on the visual analogue scale pain score during endovenous thermal ablation under tumescent anesthesia. Despite this, patients appreciate and evaluate audio and visual distraction as pleasant to extremely pleasant when applied.